RELACION ENTRE EL ORIGEN FLORAL Y EL PERFIL DE ELEMENTOS MINERALES EN MIELES CHILENAS - Montenegro, Gloria; Fredes, Carolina (Gayana Botánica, 2008)
In this report, 61 honey samples were collected in beehives located between IV and X Administrative Region of Chile. We focussed the analysis in risky chemical elements for human health and in the main chemical elements found previously in Chilean honeys. The analysis of Al, Sr, Cu, Fe, Mn and Zn were done by wet acid digestion method by ICP-OES. Lotus pedunculatus and Eucryphia cordifolia honeys showed the highest Al contents related to their geographical origin (Bío-Bío and Los Lagos Regions). The principal component analysis did not show groups of honeys with the some floral origin and a typical chemical element profile.